TNF Receptor Type II as an Emerging Drug Target for the Treatment of Cancer, Autoimmune Diseases, and Graft-Versus-Host Disease: Current Perspectives and In Silico Search for Small Molecule Binders - Shaikh, Faraz; He, Jiang; Bhadra, Pratiti; Chen, Xin; Siu, Shirley W. I. (Frontiers in Immunology, 2018)
There is now compelling evidence that TNFR2 is expressed and plays a major role in the expansion and function of CD4+Foxp3+ regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs). Consequently, targeting of TNFR2 by either antagonistists or agonists may represent a novel strategy in the treatment of cancer and autoimmune diseases, by down-regulating or up-regulating suppressor cell activity. The advance in the understanding of complex structure of TNFR2 and its binding with TNF at molecular levels offers opportunity for structure-guided drug discovery. This paper reviews the current evidences regarding the decisive role of TNFR2 in immunosuppressive function of Tregs and MDSCs, and the current effort to develop novel TNFR2-targeting therapeutic agents in the treatment of cancer, autoimmune diseases and graft-versus-host disease. To shed light on the potential TNFR2-targeting small molecules, we for the first time performed virtual screening of 400,000 natural compounds against the two TNF-binding sites, region 3 and 4, of TNFR2. Our result showed that the top hits at region 4 had slightly higher docking energies than those at region 3. Nevertheless, free energy calculation from the TNF-TNFR2 molecular dynamics simulation revealed that the binding strength of TNF in region 3 is only one-tenth of that in region 4. This suggests that region 3 is a potentially more viable binding site to be targeted by small molecules than region 4. Therefore, the effectiveness in targeting region 3 of TNFR2 deserves further investigation.